Prognostic role of cardiac magnetic resonance in left ventricular noncompaction. (13th July 2021) - Casas, G; Limeres, J; Barriales-Villa, R; Garcia-Pavia, P; Zorio, E; Gimeno-Blanes, JR; Palomino-Doza, J; Garcia-Pinilla, JM; Bayes-Genis, A; Ripoll-Vera, T; Jimenez-Jaimez, J; Villacorta, E; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left ventricular noncompaction (LVNC) is a heterogeneous entity with a wide phenotypic expression. Risk factors have not been well established and prognostic stratification remains challenging. Purpose: Describe prognostic role of CMR on long term outcomes of LVNC patients. Methods: Retrospective multicentric longitudinal cohort study of consecutive patients fulfilling imaging diagnostic criteria for LVNC (Jenni echo criteria and Petersen and Jacquier CMR criteria). Demographic, ECG, genetic, family and treatment variables were recorded. Baseline CMR was used for the analysis. LV ejection fraction (LVEF) was categorized according to heart failure (HF) guidelines and late gadolinium enhancement (LGE) was visually assessed in a binary way. End points were HF, ventricular arrhythmias (VA), systemic embolisms (SE) and all-cause death. Major adverse cardiovascular events (MACE) were the combination of the four previous end points. In patients with initially preserved LVEF (≥ 50%), LV adverse remodelling (LVAR) was defined as an LVEF < 50% and/or absolute decrease of ≥10% in LVEF at last follow-up. Results: 585 patients from 12 referral centres were included from 2000 to 2018. Age at diagnosis was 45 ± 20 years, 334 (57%) were male, baseline LVEF was 48 ± 17% and 18% presented LGE. During a median follow-up of 5.1 years (IQR 2.3-8.1), 110 (19%) patients presented HF, 87 (15%) VA, 18 (3%) SE and 34 (6%) died. MACE occurred in 223 (38%) patients. LVEF was independently associated with HF, VA, SE and MACE: HR were 1.08, 1.02, 1.04 and 1.02 respectively (all p < 0.05). LGE was more frequent in patients with reduced LVEF (39 Vs 53%, p < 0.001) and was associated with higher HF and VA risk in patients with an LVEF > 35% (HR 2.69 and 2.48 respectively, p < 0.05) (Figure 1). No MACE (0%) occurred during long-term follow-up in patients with preserved LVEF, no LGE as well as no ECG abnormalities and no family aggregation. 305 (52%) patients presented with initially preserved LVEF, and 230 (75%) of those had LVEF available at last follow-up. LVAR occurred in 50 (22%) patients: 22 (10%) had an LVEF < 50% and 41 (18%) an absolute ≥ 10% decrease in LVEF. LGE was independently associated with LVAR (HR 3.51, p = 0.045) (Figure 2). Conclusions: Cardiac magnetic resonance has an important prognostic role in LVNC. LVEF is the most powerful predictor of events. Myocardial fibrosis is associated with worse outcomes in patients without severe systolic dysfunction, as well as with left ventricular adverse remodelling in those with initially preserved LVEF. Besides, CMR may identify a low-risk subgroup of LVNC patients. Therefore, CMR should be used in risk stratification in LVNC.